ROLE AMBIGUITY AND ROLE PERFORMANCE EFFECTIVENESS: MODERATING EFFECT OF FEEDBACK SEEKING BEHAVIOUR - P. B. Srikanth,; M. G. Jomon , (Asian Academy of Management Journal, 2013)
The purpose of the present study is to understand the influence of a contextual factor (role ambiguity) and personal characteristics (feedback seeking behaviour) on role performance. As interdependent team based work has become an inherent characteristic of the workplace, role ambiguity while working is quite inherent in such organisations. By gaining better clarity regarding individual roles, employees can impact their role performance significantly. Data were collected from 176 employees of a large information technology organisation using survey technique by physically administering the questionnaire with the help of the Human Resource department in two phases; first from the employees and co-workers and finally from the supervisors. Subsequent data analysis was performed using hierarchical multiple regression. Results showed that feedback seeking both from a supervisor and co-workers ameliorated the effects of role ambiguity on role performance. Specifically, compared to feedback seeking from co-workers, feedback seeking from a supervisor was found to be more useful in reducing the effects of role ambiguity on role performance. This study draws from social cognitive theory and self-regulation theories, and implications are discussed for practicing managers in the IT industry.